Analysis of Biology Daily Assessment According to Cognitive Process Dimension and Higher Order Thingking Skills Question - Ansori, Achmad Zanuar (Journal of Biology Education, 2020)
Daily assessment plays an important role to monitor students’ learning achievement. It reflects techers’ ability in composing items and cognitive process dimension. The presence of HOTS questions in the daily assessments is very important to train students in developong higher-order thinking skills. This study aims to determine the distribution of cognitive process dimension and HOTS questions on biology daily assessment items in odd semester 2019/2020. This study also wants to uncover factors that influence biology teachers in presenting HOTS questions. The subjects of this survey study were biology teachers at MAN 1 and MAN 2 Lamongan. Data obtained through documentation and questionnaire techniques. Data in the form of question sets were analyzed with descriptive statistics (percentage). Questionnaire data was treated through the process of collecting, reducing and categorizing, displaying, and drawing conclusions. The results show that the cognitive process dimension of remembering and understanding dominate the daily assessment item in both schools, the percentage of HOTS questions is very low, and the teacher internal factors are hampering the presence of HOTS questions in the daily assessment.